PENGARUH PROSES OZONISASI TERHADAP TOTAL BAKTERI, STABILITAS VITAMIN C, DAN TEKSTUR PADA BUAH MELON POTONG - Ademai Ade Nurhayati; Arintina Rahayuni; Ria Ambarwati (Poltekkes Kemenkes Semarang, 2019)
Background: The cutted fruit one example of minimalist processed product. This product is categorized as a high risk product because it processed minimally and did not through heat contact.Objective: To determine the effect of the ozonation process on total bacteria, stability of vitamin C, and the texture of minimally processing melon fruit Bonasari Chatering, Pedurungan, Semarang. Methods: This study was an experimental study with a complete randomize design (CRD), total was 12 samples with 4 repetitions. Data collected in the form of texture measured by a penetrometer, vitamin C levels with iodometry method, and total bacteria by TPC method. Result: Texture of cutted melon which influenced by ozone gas treatment (42.0 ± 7.21) p = 0.614, for the highest level of vitamin C also in the treatment of ozone gas (36.080 ± 6.47) p = 0.560 and for the lowest total bacteria with ozone gas treatment, 3,6,105. Conclusion: There is no effect of the ozonation process on total bacteria, stability of vitamin C, and texture of minimally processing melon fruit at Bonasari Chatering, Pedurungan, Semarang.